2011
DOI: 10.1080/15287394.2011.625548
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Absolute and Relative Organ Weight Distributions For B6C3F1 Mice

Abstract: The B6C3F1 mouse is the standard mouse strain used in toxicology studies conducted by the National Cancer Institute (NCI) and the National Toxicology Program (NTP). While numerous reports have been published on growth, survival, and tumor incidence, no overall compilation of organ weight data is available. Importantly, organ weight change is an endpoint used by regulatory agencies to develop toxicity reference values (TRVs) for use in human health risk assessments. Furthermore, physiologically based pharmacoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
5
18
0
Order By: Relevance
“…In agreement with several studies, we observe an increase in body weight until 12 months of age after which body weight then remains constant (Cameron et al, 1985;Cao et al, 2003;Fahlstrom et al, 2011;Glatt et al, 2007;Halloran et al, 2002;Marino, 2012;Reynolds et al, 2002). However, other studies have noted a decrease in body weight at the end of life in various mammals including humans (Eurich and Lindner, 1984;Marino, 2012;Sawabe et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with several studies, we observe an increase in body weight until 12 months of age after which body weight then remains constant (Cameron et al, 1985;Cao et al, 2003;Fahlstrom et al, 2011;Glatt et al, 2007;Halloran et al, 2002;Marino, 2012;Reynolds et al, 2002). However, other studies have noted a decrease in body weight at the end of life in various mammals including humans (Eurich and Lindner, 1984;Marino, 2012;Sawabe et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…However, other studies have noted a decrease in body weight at the end of life in various mammals including humans (Eurich and Lindner, 1984;Marino, 2012;Sawabe et al, 2006). Although the influence of the environment certainly affects body weight, differences between species can also partly be explained by differences in rate of metabolism.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The model parameters and probability distributions are given in Tables 1 and 2. The distribution types and coefficients of variation chosen were consistent with those typically used for PBPK models (46)(47)(48)(49). Distributions were truncated at the mean Ϯ 3 standard deviations (SD) to exclude biologically implausible values.…”
Section: Computationalmentioning
confidence: 99%
“…Compared to the Gottingen minipigs, the absolute organ weights of Jue-ma are significant higher than Gottingen minipigs, while most relative organ weights are lower than Gottingen minipigs. Previous reports demonstrated that the absolute and relative organ weights are affected by many factors, such as sex, age class, body weight, and nutritional status (Marino, 2012;Lessard-Beaudoin et al, 2015). The differences between Jue-ma and Gottingen minipigs might cause by body weights.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%